Baptism and the interpretation of early Quistian art - Stander, Hennie (Hervormde teologiese studies, 1987)
The aim of this article is to stress the necessity of interpreting early Christian art in its context and with due respect to its deep structure or primary notion. It often happens that scholars base their arguments on the superficial features of a work of art, but they fail to understand the notion which these features convey. This will be illustrated by examples of baptismal scenes. It will be shown how these scenes of art are misused and misinterpreted by modem scholars because the above-mentioned principles are disregarded.